The Role of Organizational Culture on Employee Performance through Job Satisfaction and Work Motivation - Maha Putra, Delka; Nasution (Program MM Universitas Surabaya, 2024)
Purpose: This study analyzes the relationship between organizational culture and employee performance. The research also aims to evaluate the roles of job satisfaction and work motivation as mediating variables in the relationship between organizational culture and employee performance. Method: This research adopts a quantitative-explanatory approach with 155 respondents. SEM-PLS was used in this research to examine each variable's relationship and analysis using art-PLS 4. Result: The results indicate that Organizational Culture positively and significantly influences Job Satisfaction, Work Motivation, and Employee Performance. Furthermore, Job Satisfaction and Work Motivation also positively and significantly impact Employee Performance. Mediation analysis reveals that Job Satisfaction and Work Motivation partially mediate between Organizational Culture and Employee Performance.